'The pandemic is not still here': individuals' knowledge, attitudes and practices in response to COVID-19 in a metropolitan Ethiopian city. (29th March 2022) - Eyasu, Nahom
This research addresses the knowledge gap of individuals' knowledge, attitudes and practices (KAP) towards COVID-19 in Ethiopia. The study involved 35 participants derived using a non-probability convenience sampling technique. Data were analysed using inductive thematic analysis to explore the major themes of comprehension, perception and disease handling. The results show that COVID-19 can be curved its spread by using the three types of 'standing up': standing up with, standing up for, and standing up as. The results also reveal that KAP gained from religious and cultural beliefs might have a more significant impact on protection against COVID-19 than official protocols do. In addition, conventional, expressive and oriented rational social actions also reduce the spread of COVID-19. Standing up with the government, standing up as taking consideration of the individuals' responsibilities and standing up for executing the protocol of COVID-19 can mitigate the cause and consequences of COVID-19.